Measuring fiscal incidence and its redistributive impact in Swaziland - Lukhele, Mathale'a (Research of GSB, 2017)
According to Swaziland's National Development Strategy, the country's objectives are to improve the standard of living of all citizens, eradicate poverty, create employment, enhance gender equality and improve the country's human development ranking from a low human development rank to a high human development rank by 2022. Persistent poverty and the unequal distribution of income have, however, posed significant challenges for the country in achieving these development goals. This study assessed the extent to which the government of Swaziland has been able to use its fiscal policy, in particular the tax and public expenditure policies on health and education, to redistribute resources and reduce income inequality. The study also investigated the incidence of out-of-pocket expenses incurred by households in accessing public health and education facilities. Based on both the Swaziland Household Income and Expenditure Survey data collected in the 2010 national survey and the government's 2010 budget, the study found that the tax policy had had a slight redistributive effect, as the Gini coefficient, had dropped from 0.7909 (pre-tax income distribution) to 0.7424 (post-tax income distribution). Public expenditure on education improved the income of poor households by 32.83 per cent and had led to a further reduction in the Gini to 0.7185; however, public expenditure on tertiary education was poorly targeted as rich households were deriving a higher benefit than poor households. Out-of-pocket expenses on health were not regressive despite the fact that there was a low usage of health facilities by the low income households. On the other hand, education out-of-pocket expenses were found to be regressive and had a negative impact on the progression rates from primary education to higher learning institutions in the low income households. Overall it would appear that the country's fiscal policy has led to a reduction in the country's income inequality. However, the country has not made significant progress towards the achievement of its development goals, with the 2010 national household survey revealing that the poverty rate was still relatively high at 0.630, while the 2010 labour force survey revealed that unemployment was still high at 0.406 and the 2014 human development report showed that the country was still ranked low in terms of human development.